Nexus 2002 Post-Conference Excursion: The Monasteries of Alcobaça and Batalha - João Pedro Xavier (2002)
The Monasteries of Alcobaça and Batalha are related to important events in Portuguese political history: the first one, actually, to the birth of Portugal, the second one to its continuity as an independent nation. Both Monasteries are huge buildings, best representative of each dynasty apart from some military resorts. The Monastery of Alcobaça church is almost an exact reproduction of the one from Clairvaux. The entire monastery is in fact very similar to the model, which allows us to consider its Cistercian gothic architecture, here transcribed in white stone, as an example of "international style" of that time. Batalha's plan is inscribed in the mendicant tradition but its proportions and stoned vaulted spaces make it an exceptional example. It's deeper and most of all it's higher! Here the gothic verticality becomes a fact and, of course, we have all over the temple the light inflowing through large stained glasses now allowed by the accuracy of the constructive system.